THE ROLE OF THE ROMANIAN NATIONAL BANK IN APPLYING THE BANKRUPTCY PROCEDURE OF THE BANKING CREDIT INSTITUTIONS - RARES-SEBASTIAN PUIU-NAN (Challenges of the Knowledge Society, 2013)
The article examines the role of the National Bank of Romania in the insolvency procedure of the banking institutions. The most important regulations regarding this issue consist in the Government’s Order 10/2004 regarding the bankruptcy of credit institutions. According to it, the following officials are to be appointed in the insolvency procedure of banking institutions: insolvency courts of justice, insolvency judge and liquidator. Although the National Bank of Romania is not considered a participant, it has a very important role in this procedure. My article presents in the beginning the Status of the National Bank of Romania. The next chapters are dedicated to the role of the National Bank of Romania in insolvency: withdrawal of the operating license of the credit institution, taking part in the insolvency procedure as an active participant or as a creditor side, appointing and dismissing of the interim administrator, mandatory or advisory opinion, role of information.